Innovation of the Indonesian National Qualifications Framework Curriculum at the State Islamic University in Aceh - Azhar Azhar; Fakhrul Rijal; Misnan Misnan; Tasnim Idris (STAI Hubbulwathan Duri, 2023)
This research aims to describe the Indonesian National Qualifications Framework (KKNI) curriculum innovation at the state Islamic University in Aceh. This research uses a qualitative approach. Data collection techniques included in-depth interviews, observation, and documentation with 5 groups of respondents, namely: the dean, deputy dean for academic affairs, head of the study program, and senior lecturers from the 3 state Islamic universities used as research locations. Data were analyzed using descriptive analysis consisting of data reduction, data presentation, and drawing conclusions. The research results show that the KKNI curriculum innovation at state Islamic universities is grouped into two parts, namely: adapting courses and optimizing the learning process. Course innovation is carried out in the form of adapting courses to the learning outcomes of graduates in each study program. This course adjustment includes adjusting and developing teaching materials that are relevant to the objectives to be achieved in each course. Innovation in the learning implementation process is carried out through the preparation of semester learning plans carried out by lecturers in accordance with the courses they teach, guided by the learning outcomes of study program graduates. Method innovation through the use of active, creative and innovative methods.